Assessing and Reforming Public Financial Management : A New Approach - Allen, Richard; Schiavo-Campo, Salvatore; Columkill Garrity, Thomas (Washington, DC: World Bank, 2013)
This study is intended to help underpin a more coordinated, effective approach to assessing and reforming systems for public expenditure, procurement, and financial accountability in developing countries-especially countries that receive international aid for budget support. Such support, also known as adjustment lending, has become far more important in recent years. At the World Bank, for example, it increased from less than 10 percent of total assistance in the 1980s to about 50 percent in fiscal 2002. Many other development agencies are also increasing aid for budget support. This support has been accompanied by and reflects widespread recognition that aid is fungible and that resources can be transferred, so that aid intended for one project can effectively be used to finance another. Thus, efforts to safeguard the integrity of donor resources mean little without safeguards on the use of government resources. Moreover, growing awareness of the destructive effects of corruption -- emphatically underscored by the East Asian financial crisis of 1997-99 -- has given new urgency to donors' need to ensure that aid is not diverted to private ends or misallocated to activities not conducive to fostering growth and reducing poverty. For all these reasons it is important for donors and recipient governments alike that the strengths and weaknesses of national budget systems be well understood and that governments implement reforms where needed, especially in high-risk areas.